2013
DOI: 10.5194/os-9-301-2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring programme of the hydrological variability in the Mediterranean Sea: a first overview of the HYDROCHANGES network

Abstract: Abstract. The long-term monitoring of basic hydrological parameters (temperature and salinity), collected as time series with adequate temporal resolution (i.e. with a sampling interval allowing the resolution of all important timescales) in key places of the Mediterranean Sea (straits and channels, zones of dense water formation, deep parts of the basins), constitute a priority in the context of global changes. This led CIESM (The Mediterranean Science Commission) to support, since 2002, the HYDROCHANGES prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 107 publications
2
29
0
Order By: Relevance
“…• data from one of the HYDROCHANGES deep moorings (Schroeder et al 2013). Initiated in 2003, the HYDROCHANGES programme aims at recording time series of the hydrological characteristics of the water masses and of their variability in key places (straits, DWF areas, trenches, .…”
Section: Deep Water Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…• data from one of the HYDROCHANGES deep moorings (Schroeder et al 2013). Initiated in 2003, the HYDROCHANGES programme aims at recording time series of the hydrological characteristics of the water masses and of their variability in key places (straits, DWF areas, trenches, .…”
Section: Deep Water Characteristicsmentioning
confidence: 99%
“…Long-term and continuous monitoring of the phenomenon started only recently thanks to the HYDROCHANGES programme with deep moorings (Schroeder et al 2013) and to the integrated observing system MOOSE (Mediterranean Ocean Observing System for the Environment, www.moose-network.fr) since 2010 with annual and monthly CTD cruises and continuous recording by surface buoys and deep moorings (Testor et al 2012;Durrieu de Madron et al 2013). Therefore, our current knowledge of the long-term variability of the phenomenon before 2007 mainly comes from yearly case studies and sparse field campaigns (Leaman and Schott 1991;Schott et al 1996;Schroeder et al 2008;Durrieu de Madron et al 2013) or from satellite-derived reconstructions .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at the south-eastern part of the basin, dense water outflow has been recorded during 2009 from the Aegean Sea, that followed a northward path along the Hellenic Trench giving a signal of increased salinity in the intermediate layers . This outflow was the result of the preconditioned for dense water formation status of the Aegean that has been reported for the period 2007-2012 (Schroeder et al, 2013;Krokos et al, 2014;Cardin et al, 2015;Kassis et al, 2015) and resulted in the alternation of the southeastern Ionian upper and intermediate waters. The aforementioned short term inter-annual changes in the area's hydrography create a challenging field for the performance of numerical hydrodynamic simulations.…”
Section: Study Areamentioning
confidence: 99%
“…Data collected in the framework of the HYDROCHANGES program [Schroeder et al, 2013] from a permanently moored CTD station at the bottom (850 m) of the Antikythira strait, showed that there were episodic According to Kontoyiannis et al [1999b], water masses denser than LIW with densities up to 29.16-29.18 kg/m 3 were formed during 1986, 1992, and 1995 in the Rhodes Gyre area, reaching depths of 1000 m in 1986 and 1995 and even deeper ( 2000 m) during the peak-EMT period in 1992. To investigate the possible existence of similar water masses being formed in the same area during the period examined in this work, deep ARGO profiles at the wide area of the Rhodes Gyre between 2005 and 2012 were examined.…”
Section: Cretan Straits Exitmentioning
confidence: 99%